Factor Affecting Construction Quality On Construction Projects In Central Java With Analytical Hierarchy Process (AHP) Method - Chasanah, Ummi; Soehartono, Soehartono (SEAN Institute, 2024)
Improvement in project construction should follow increasing quality construction so that project construction can be interpreted as successful if the project construction is the appropriate time, cost, and quality by planning. Research This aims To identify possible factors that influence quality construction using the Analytical Hierarchy Process (AHP), especially in construction projects in Central Java. Using questionnaires and Analytical Hierarchy Process (AHP) analysis for respondents who are experts in the construction sector, it was found that the factors that influence construction quality are money, materials, man, methods, and machines. Developing and implementing project construction: The project must already follow quality and proper construction quality in planning. Existence coordination and work are needed to carry out project construction so that quality construction is achieved by planning. Analysis with the AHP method is carried out for all respondents from each criterion, sub-criteria, and alternative, as well as to get a goal from quality construction. With Analysis of the Analytical Hierarchy Process, the results of each factor influencing construction quality from the highest to the lowest are man at 0.262, materials at 0.253, money at 0.231, methods at 0.142, and machines at 0.112.